Contact pathway of coagulation and inflammation - Wu, Yi (Thrombosis journal, 2015)
The contact system, also named as plasma kallikrein-kinin system, consists of three serine proteinases: coagulation factors XII (FXII) and XI (FXI), and plasma prekallikrein (PK), and the nonenzymatic cofactor high molecular weight kininogen (HK). This system has been investigated actively for more than 50 years. The components of this system and their interactions have been elucidated from in vitro experiments, which indicates that this system is prothrombotic by activating intrinsic pathway, and proinflammatory by producing bioactive peptide bradykinin. Although the activation of the contact system have been implicated in various types of human disease, in only a few instances is its role clearly defined. In the last 10 years, our understanding of the contact system, particularly its biology and (patho)physiology has greatly increased through investigations using gene-modified animal models. In this review we will describe a revitalized view of the contact system as a critical (patho)physiologic mediator of coagulation and inflammation.